Neuropsychology of friendship: Exploring the intricacies of brain and friendship - Angela*, Lisa; Auliani, Fitri; Amrullah, Ahmad Yusrifan; Fuadi, Muhammad Nurrifqi; Aulia, Wina; Fauziah, Syifa (Riwayat: Educational Journal of History and Humanities, 2023)
Every individual has a need to build friendship relationships with other individuals as an important aspect of social life. Positive and supportive friendships have implications for improving mental well-being, and happiness, reducing stress levels, reducing depressive symptoms, and helping to reduce loneliness. Studies related to the impact of friendship in social relationships on mental health have been widely reviewed. However, studies on the underlying mechanisms such as the brain systems that influence friendships are limited. This literature review aims to overview how the brain works on friendship from a neuropsychological perspective. The research method uses a literature review approach with the manuscript writing method referring to narrative review. The literature review results found that the brain system has a crucial role in human social interactions such as understanding, feeling, and responding to friendship relationships. The parts of the brain that actively contribute to friendship relations are the ventromedial prefrontal cortex (vmPFC), nucleus accumbens (NAcc); amygdala, hippocampus, superior parietal lobule (SPL), putamen, precentral gyrus, and posterior middle temporal gyrus (pMTG).